2022
DOI: 10.2196/36671
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Provision and Context of Use of Hearing Aid Listening Programs From Real-world Data: Observational Study

Abstract: Background Listening programs enable hearing aid (HA) users to change device settings for specific listening situations and thereby personalize their listening experience. However, investigations into real-world use of such listening programs to support clinical decisions and evaluate the success of HA treatment are lacking. Objective We aimed to investigate the provision of listening programs among a large group of in-market HA users and the context in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
0
0
0
Order By: Relevance
“…This is in agreement with Welling et al (2020 ) who found that participants rarely changed their hearing program in anticipation of a situation. In contrast, Pasta et al (2022 ) analyzed the acoustic environment before and after a program change and found that some users tended to change programs in anticipation. In the current EMA field trial, the need to get to know the hearing programs might have made it more difficult to make preemptive modifications.…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with Welling et al (2020 ) who found that participants rarely changed their hearing program in anticipation of a situation. In contrast, Pasta et al (2022 ) analyzed the acoustic environment before and after a program change and found that some users tended to change programs in anticipation. In the current EMA field trial, the need to get to know the hearing programs might have made it more difficult to make preemptive modifications.…”
Section: Discussionmentioning
confidence: 99%